Logan Avenue Problem Solving Learning Model (Laps-Heuristic) on Mathematics Learning Outcomes of Class VII Students at Wusto Imam An-Nasai Gowa - Nur Aisyah; Rizka Ridha Ruslan; Indah Viqrianti Ramli; Rahmah Musda; Azwan Anwar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study examined the effectiveness of applying the Logan Avenue Problem Solving (LAPS-Heuristic) learning model on mathematics learning outcomes among Class VII students at Wusto Imam An-Nasai Gowa using a one-group pretest–posttest design. The population consisted of all seventh-grade students enrolled in the even semester of the 2024/2025 academic year. A learning outcome test was employed as the primary research instrument to measure students’ performance before and after the implementation of the learning model. The data analysis involved descriptive statistical methods combined with gain tests to assess the extent of improvement. The findings revealed that students’ mathematics achievement fell predominantly within the very high category, with 53.85% of learners classified in this range, indicating a notable increase in category levels compared to their pretest performance. Furthermore, the percentage of students who successfully met the required minimum competency standards after the application of the LAPS-Heuristic model reached 96.15%. This outcome clearly illustrates that the vast majority of students—over 85%—achieved or exceeded the established passing threshold, suggesting that the integration of the LAPS-Heuristic approach was highly effective in enhancing mathematics learning outcomes. Overall, the results underscore that the LAPS-Heuristic learning model can serve as a practical and impactful strategy to improve student engagement, comprehension, and mastery of mathematical concepts in junior high school settings.